2001
DOI: 10.1046/j.1442-2026.2001.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumomediastinum, pneumothorax and ecstasy abuse

Abstract: A case report is presented of a patient with bilateral pneumothoraces and spontaneous pneumomediastinum associated with ecstasy use. Pneumothorax and spontaneous pneumomediastinum should be considered in an ecstasy user who complains of chest pain, neck pain or shortness of breath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Thirteen previous reports outlining case histories of 15 patients were identified in the world literature dating from 1993 ( Table 2). [1][2][3][4][5][6][7][8][9][10][11][12][13] Eight of the 15 patients underwent gastrograffin swallow to exclude oesophageal dysfunction. One patient had a small tear demonstrated and was treated conservatively.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen previous reports outlining case histories of 15 patients were identified in the world literature dating from 1993 ( Table 2). [1][2][3][4][5][6][7][8][9][10][11][12][13] Eight of the 15 patients underwent gastrograffin swallow to exclude oesophageal dysfunction. One patient had a small tear demonstrated and was treated conservatively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that spontaneous pneumomediastinum arises from perivascular alveolar rupture and subsequent escape of air through the vascular sheaths into the mediastinum, and thereafter to the fascial planes of the neck, as the air follows the path of least resistance [2]. Perivascular alveolar rupture can be caused by sudden increases in the bronchovascular pressure gradient, through an increase in alveolar pressure such as in mechanical ventilation and Valsalva manoeuvre, or a decrease in pulmonary interstitial pressure such as in asthma and bronchiolitis [3]. …”
Section: Discussionmentioning
confidence: 99%
“…All 22 previous cases of ecstasy-related pneumomediastinum reported in the literature presented with either chest pain and/or breathlessness [3, 516]. The chest pain is usually pleuritic in nature and has been reported to radiate to the neck [8] or back [8, 10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations